2012
DOI: 10.1007/s10973-012-2673-z
|View full text |Cite
|
Sign up to set email alerts
|

Influence of amorphous block on the thermal behavior of well-defined block copolymers based on ε-caprolactone

Abstract: In this work, we studied the thermal characterization of block copolymers based on e-caprolactone. The copolymers were obtained by anionic polymerization techniques, using different co-monomers such as styrene (S) and dimethylsiloxane (DMS). Synthesized copolymers were characterized by H-nuclear magnetic resonance, size exclusion chromatography, and Fourier transform infrared spectroscopy. Isothermal crystallization was performed by differential scanning calorimetry (DSC), and Avrami's theory was employed in o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
38
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 13 publications
(45 citation statements)
references
References 48 publications
4
38
0
3
Order By: Relevance
“…The continuous activation energy curve resulting from the linear heating rate is showed in Figure for PCL and COP5. PCL homopolymer presented an average activation energy value of ∼159 KJ mol −1 ,which is similar to values reported in the literature . Rázga & Petránek and Çekingen et al reported values of activation energy for the degradation process of PHEMA homopolymer of ∼129 KJ mol −1 .…”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…The continuous activation energy curve resulting from the linear heating rate is showed in Figure for PCL and COP5. PCL homopolymer presented an average activation energy value of ∼159 KJ mol −1 ,which is similar to values reported in the literature . Rázga & Petránek and Çekingen et al reported values of activation energy for the degradation process of PHEMA homopolymer of ∼129 KJ mol −1 .…”
Section: Resultssupporting
confidence: 83%
“…Finally, a linear PCL homopolymer was synthesized following classical anionic polymerization procedures . This homopolymer was synthesized by using this technique in order to have a perfect control of its molar mass and polydispersity, with the purpose of having a true model PCL homopolymer.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figures and show the TGA and first‐derivative curves under nitrogen and oxygen atmospheres, respectively. Model PCL showed one thermal event at around 405–410 °C, as it is reported in the literature . As it can be observed, PHEMA incorporation did not affect the maximum degradation rate ( T max ) of the linear polyester (Figure b and Table ), but a decrease in the initial zone between 180 and 350 °C was observed.…”
Section: Resultssupporting
confidence: 77%
“…The resulting BSTSE was further purified by column chromatography on silica using petroleum ether as eluent and recrystallized under cold conditions. On the other hand, a model PCL homopolymer was synthesized as reference material by employing classical anionic polymerization as described elsewhere (DP ≈ 100) …”
Section: Methodsmentioning
confidence: 99%